A cross-linked spore phenol adsorbent based on nucleic acid aptamer functionalized magnetic hydrophobic polymer and its application

By functionalizing the magnetic hydrophobic polymer on magnetic nanoparticles and combining with the specific recognition of nucleic acid aptamer, the problem of low adsorption efficiency of adsorbents is solved, and the efficient and selective adsorption effect of crospool is achieved.

CN116440874BActive Publication Date: 2025-02-18BEIJING ACADEMY OF AGRICULTURE & FORESTRY SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310457145.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-25
Publication Date
2025-02-18
Estimated Expiration
2043-04-25

AI Technical Summary

Technical Problem

In the prior art, when the nucleic acid aptamer functionalized magnetic nanoparticles are used as adsorbents, there are few interaction sites with the target, resulting in low adsorption efficiency.

Method used

Using nucleic acid aptamol adsorbent functionalized magnetic hydrophobic polymers, the interaction sites and hydrophobic interactions with the target are increased through the synergistic effect of nucleic acid aptamer and magnetic hydrophobic polymers, thereby improving adsorption efficiency.

Benefits of technology

Highly efficient adsorption and desorption of crospool is achieved, with an adsorption capacity of up to 187.6 ng/mg, and has good selectivity and stability, and can be reused for more than 6 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004199897160000101
    Figure BDA0004199897160000101
  • Figure BDA0004199897160000102
    Figure BDA0004199897160000102
  • Figure BDA0004199897160000121
    Figure BDA0004199897160000121
Patent Text Reader

Abstract

The present invention provides a cross-linked spore phenol adsorbent based on a nucleic acid aptamer functionalized magnetic hydrophobic polymer and its application, which is obtained by coupling a nucleic acid aptamer with a magnetic hydrophobic polymer, wherein the magnetic hydrophobic polymer is a copolymer of magnetic nanoparticles, methyl methacrylate and vinyl ethylene carbonate, wherein the nucleic acid aptamer can specifically identify AOH, and the magnetic hydrophobic polymer is designed according to the molecular structure of AOH, and can increase the hydrophobic interaction with AOH, and under the synergistic effect of the nucleic acid aptamer and the magnetic hydrophobic polymer, the efficient and highly specific adsorption of AOH is achieved. The cross-linked spore phenol adsorbent based on a nucleic acid aptamer functionalized magnetic hydrophobic polymer provided by the present invention can be used for the efficient and highly specific adsorption of toxin target molecules having a hydrophobic class under the premise of changing the corresponding aptamer to which it is bonded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sample pretreatment, and in particular relates to a cross-linked spore phenol adsorbent based on a nucleic acid aptamer functionalized magnetic hydrophobic polymer. Background Art

[0002] Alternaria solani (AOH) is the main toxic metabolite of Alternaria solani, which has strong teratogenicity, mutagenicity and genotoxicity. HPLC-MS and other methods are traditional detection methods for AOH. However, the content of Alternaria solani toxins in actual samples spans a wide range, the sample matrix is ​​complex and there are many interferences, which restricts the accuracy and precision of the analysis of Alternaria solani toxins in actual samples. Therefore, the development of effective adsorption or enrichment materials and methods for AOH to achieve the goal of separating and enriching the analyte and eliminating matrix interference has become a research hotspot for the analysis of fungal toxins in various actual samples in recent years.

[0003] Prior art 1: Immunoaffinity column (IAC) is a simplified sample extraction process commonly used in the pretreatment of mycotoxin samples and has good recognition specificity.

[0004] Prior art 2: Molecular imprinting polymers (MIPs) synthesized with target molecules as templates can mimic the recognition sites of antibodies, complement the target molecules in size, shape and functional group positions, and have the potential to replace IACs. Bondi (Food Chem. 2018; 243: 357-364) et al. used 4-vinylpyridine (VIPY) and methacrylamide (MAM) as functional monomers, ethylene glycol dimethacrylate (EDMA) as a crosslinker, and 3,8,9-trihydroxy-6H-dibenzo[B,D]pyran-6-one (S2) as an AOH replacement template to prepare MIPs for selective adsorption of AOH in food samples, with good recovery rates.

[0005] Prior art 3: Nucleic acid aptamers refer to single-stranded DNA (ssDNA) or RNA obtained by in vitro screening using the SELEX technology. Nucleic acid aptamers can bind to targets with high specificity and high affinity, and have a wide range of targets (including proteins, peptides, small molecules, cells, bacteria and even tissues). They can be synthesized by chemical methods and have the characteristics of low cost, easy modification and good stability. Once the aptamer sequence is determined, it can be synthesized with high purity and high repeatability at a low cost. As "chemical antibodies", nucleic acid aptamers play an important role in the specific recognition and adsorption of various targets due to their excellent properties. Using nucleic acid aptamers as molecular recognition elements and combining them with magnetic nanoparticles (MNPs) as carriers can achieve the adsorption and separation of fungal toxins in complex sample matrices.

[0006] Currently, there are few commercial IACs for AOH sample pretreatment, indicating that the development and preparation of high-specificity and high-affinity antibodies against AOH is difficult.

[0007] The sample pretreatment technology based on MIP has a complex preparation process, consumes template molecules, and is not universal.

[0008] Using aptamer-functionalized MNPs as adsorbents, the specific recognition of aptamers and the magnetic separation characteristics of MNPs can achieve the enrichment and separation of target toxins. However, there are fewer functional groups on the surface of MNPs and fewer interaction sites with the target, which cannot further improve the adsorption efficiency of aptamer-functionalized MNPs as adsorbents. Summary of the invention

[0009] In order to solve the technical problem that when aptamer-functionalized MNPs are used as adsorbents, there are few interaction sites with the target, resulting in low adsorption efficiency, the present invention provides an adsorbent based on aptamer-functionalized magnetic hydrophobic polymers.

[0010] To achieve the above object, the present invention adopts the following technical solutions:

[0011] The invention discloses an aptamer-functionalized magnetic hydrophobic polymer-based crosslinked spore phenol adsorbent, which is a nucleic acid aptamer coupled with a magnetic hydrophobic polymer, wherein the magnetic hydrophobic polymer is a copolymer of magnetic nanoparticles, methyl methacrylate and vinyl ethylene carbonate, and the nucleic acid aptamer is used for binding crosslinked spore phenol (AOH).

[0012] A magnetic hydrophobic polymer material for nucleic acid aptamer functionalization is prepared by the following method: adding magnetic nanoparticles to polyallylamine hydrochloride (PAHC) solution for first ultrasonic washing, then adding polyvinyl pyrrolidone (PVP) solution for second ultrasonic reaction, and first stirring reaction, washing with water, adding the PAHC and tetraethyl orthosilicate (TEOS) to anhydrous ethanol containing ammonia water, and after the second stirring reaction, washing with ethanol to remove excess reactants; then dispersing the PAHC in ethanol, adding 3-(trimethoxysilyl) propyl methacrylate (MPS), and stirring for the third time to synthesize MNPs@MPS;

[0013] The magnetic hydrophobic polymer material MHbP was synthesized by reacting MNPs@MPS with VEC, MMA, AIBN and 1,4-dioxane.

[0014] As described above, the magnetic hydrophobic polymer material, preferably, the magnetic nanoparticles and PAHC are added in a mass ratio of 2:1, the amount of polyvinyl pyrrolidone (PVP) and PAHC are added in a mass ratio of 1:4, the ratio of tetraethyl orthosilicate (TEOS) and 1.3% ammonia water and anhydrous ethanol is 1:100, and the addition ratio of 3-(trimethoxysilyl)propyl methacrylate (MPS) and ethanol is 1:25.

[0015] For the magnetic hydrophobic polymer material as described above, preferably, the first ultrasonic time is 1 to 60 minutes, the second ultrasonic time is 15 to 30 minutes, the first stirring time is 5 to 10 hours, the second stirring time is 5 to 10 hours, and the third stirring time is 10 to 24 hours.

[0016] More preferably, the first ultrasonication time is 60 min, the second ultrasonication time is 20 min; the first stirring time is 10 h, the second stirring time is 10 h, and the third stirring time is 24 h.

[0017] As the magnetic polymer material described above, preferably, MNPs@MPS is reacted with VEC, MMA, AIBN and 1,4-dioxane in a mass to volume ratio of 100:70 to 570:500:10:10, wherein the first four are in mass units of mg and the last one is in volume units of mL; the reaction conditions for synthesizing MHbP are to react in an oil bath at 90°C for 24 hours under nitrogen protection.

[0018] Further, most preferably, MNPs@MPS is mixed with VEC, MMA, AIBN and 1,4-dioxane in a mass to volume ratio of 100:285:500:10:10.

[0019] A cross-linked spore phenol adsorbent based on a nucleic acid aptamer functionalized magnetic hydrophobic polymer, and a preparation method thereof comprises: incubating the prepared magnetic hydrophobic polymer material MHbP with an AOH aptamer to obtain a nucleic acid aptamer functionalized magnetic hydrophobic polymer adsorbent, namely MHbPA.

[0020] Preferably, the reaction ratio of the MHbP to the AOH aptamer solution is 5.0 mg:320.0 μL, the concentration of the AOH aptamer is 10.0 μM, the incubation time is 24 h, and the reaction is carried out at room temperature.

[0021] Preferably, the nucleic acid sequence of the AOH aptamer is: 5'-NH2-(CH2)6-GGC ACT CCA CGC ATA GGCATA CTT AAC TAG TGT TCA AGT TAT CCT GTG CGT GGA TGT CC-3'.

[0022] Further, the preparation method of the cross-linked spore phenol adsorbent as described above preferably comprises the following steps:

[0023] S1. Preparation of magnetic nanoparticles (MNPs): First, 1.4 g (5.0 mM) FeCl3·6H2O was dissolved in 40 mL ethylene glycol, and then 3.6 g NaAC and 1.0 g polyethylene glycol 200 were added. After stirring for 30 min, the obtained yellow viscous liquid was sealed in a stainless steel autoclave lined with polytetrafluoroethylene and reacted at 200°C for 8 h. After the autoclave was cooled naturally, the generated MNPs were collected with a magnet, and the excess reactants were washed away with ethanol to obtain MNPs.

[0024] S2. Disperse the above MNPs in 50 mL of water, add 0.5 g of PAHC, sonicate for 1 h, and wash away excess reactants with deionized water; add 10.0 mL of water and 40.0 mL of 50.0 mg / mL PVP to the above product, sonicate for 20 min, stir at 600 rpm for 10 h at room temperature, and wash away excess reactants with water; add the above product to 100 mL of anhydrous ethanol containing 1.3% ammonia, add 1.0 mL of TEOS, stir at room temperature for 10 h, and wash away excess reactants with ethanol; disperse the above product in 100.0 mL of ethanol, add 4.0 mL of MPS, stir at room temperature for 24 h, wash away excess reactants with ethanol, and dry at 45 ° C for 12 h to obtain MNPs@MPS;

[0025] S3. Preparation of magnetic hydrophobic polymer: 100.0 mg MNPs@MPS, 285.0 mg VEC, 500.0 mg MMA, 10.0 mg AIBN and 10.0 mL 1,4-dioxane were added to a flask, and protected with nitrogen, and reacted in an oil bath at 90 °C for 24 h; the excess reactants on the surface were washed with ethanol and water, and the obtained product was dried at 45 °C for 12 h to obtain MHbP;

[0026] S4, 320.0 μL of 10.0 μM AOH aptamer was mixed with 5.0 mg MHbP and incubated at room temperature for 24 h; after the reaction was completed, the mixture was washed three times with binding buffer to remove excess reactants and obtain MHbPA;

[0027] The binding buffer is an aqueous solution containing 10.0 mM Tris-HCl, 10.0 mM NaCl, 5.0 mM MgCl2, pH 7.3.

[0028] Application of the cross-linked spore phenol adsorbent as described above or the cross-linked spore phenol adsorbent obtained by the preparation method in sample pretreatment for detecting AOH.

[0029] Furthermore, the application is the application and addition of the cross-linked spore phenol adsorbent in sample pretreatment, taking 5.0g of the sample to be tested and mixing it with 10.0mL of water / acetonitrile (40 / 60, v / v) in a centrifuge tube, vortexing for 10 minutes, taking the supernatant and filtering it through a filter membrane, taking 1.0mL of the above sample solution and mixing it with 320μL of the cross-linked spore phenol adsorbent with a concentration of 5-20mg / mL and incubating it for 10 minutes, washing the MHbPA adsorbed with AOH three times with a binding buffer, and then mixing it with 0.8mL70% methanol (methanol / binding buffer, v / v, 70 / 30) and incubating it for 10 minutes to elute the adsorbed AOH, and after magnetic separation, taking the supernatant for HPLC determination, and calculating the AOH content eluted after MHbPA adsorption, which is the AOH content of the sample to be tested after MHbPA pretreatment.

[0030] The beneficial effects of the present invention are:

[0031] The present invention provides an AOH adsorbent based on a nucleic acid aptamer functionalized magnetic hydrophobic polymer, the magnetic hydrophobic polymer is designed according to the molecular structure of AOH, has targeting, and can increase the hydrophobic interaction with AOH. In addition, this type of hydrophobic polymer is suitable for the adsorption of other hydrophobic toxin target molecules.

[0032] The invention provides an AOH adsorbent based on a nucleic acid aptamer functionalized magnetic hydrophobic polymer, which uses the nucleic acid aptamer of AOH as a specific recognition element, and ensures the specificity of adsorption and recognition on the basis of improving the adsorption capacity of the magnetic hydrophobic polymer.

[0033] The present invention provides an AOH adsorbent based on a nucleic acid aptamer functionalized magnetic hydrophobic polymer. The constructed adsorbent can achieve efficient adsorption and desorption of AOH within 10 minutes, with an adsorption capacity of up to 187.6 ng / mg; and has good selectivity and stability, and can be reused for more than 6 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of the preparation process of MHbPA in Example 1;

[0035] Figure 2 is the infrared spectrum characterization result of MHbP;

[0036] Figure 3 The XPS characterization results of MNPs, MHbP, and MHbPA;

[0037] Figure 4 The VAM characterization results of MNPs, MHbP, and MHbPA;

[0038] Figure 5TGA characterization results of MNPs, MHbP, and MHbPA;

[0039] Figure 6 Transmission electron microscopy results of the prepared material and particle size

[0040] Figure 7 is the effect of MHbP mass on adsorption efficiency;

[0041] Figure 8 The effect of hydrophobic monomer types on AOH adsorption efficiency;

[0042] Fig. 9 is the effect of sample volume on AOH adsorption efficiency;

[0043] Fig.10 The effect of different desorption solvents on the desorption efficiency;

[0044] Fig.11 is the effect of methanol ratio on desorption efficiency;

[0045] Fig.12 The effect of different desorption time on desorption efficiency;

[0046] Fig.13 The effect of different desorption volumes on the desorption efficiency.

[0047] Fig.14 The adsorption performance results of MHbPA on different AOH concentrations;

[0048] Fig.15 Fitting results of different isothermal adsorption models for the adsorption behavior of MHbPA on AOH;

[0049] Fig.16 is the adsorption efficiency of MHbPA on AOH at different adsorption times;

[0050] Fig.17 Fitting of different adsorption kinetic models for MHbPA adsorption to AOH;

[0051] Fig.18 is the selectivity of MHbPA;

[0052] Fig.19 for the stability of MHbPA;

[0053] Fig. 20 is the number of times MHbPA is reused;

[0054] Fig.21 The adsorption capacity of AOH by different adsorbents. DETAILED DESCRIPTION

[0055] The present invention aims to develop an adsorbent based on aptamer-functionalized magnetic hydrophobic polymers, and solves the problem of low adsorption efficiency when the aptamer is used alone as a recognition element through the synergistic enhancement of the aptamer and the magnetic hydrophobic polymer, so as to achieve rapid and efficient separation and enrichment of AOH in a complex matrix. The magnetic hydrophobic polymer (poly (methyl methacrylate-ethylene carbonate) @ MNPs, i.e. p (MMA-VEC) @ MNPs, abbreviated as MHbP) is designed according to the hydrophobicity of AOH, and the amino-modified aptamer is coupled to MHbP through the reaction with the VEC monomer to construct an aptamer-functionalized magnetic hydrophobic polymer adsorbent, i.e. MHbPA. In the constructed adsorbent, the synergistic rapid and efficient separation and enrichment of AOH can be achieved through the specific affinity of the aptamer and the hydrophobic interaction between the magnetic hydrophobic polymer and AOH.

[0056] Design and synthesis of targeted magnetic hydrophobic polymers in the present invention: Magnetic hydrophobic polymers mainly include three parts: ① magnetic nanoparticles containing double bonds; ② polymer monomers providing aptamer bonding groups; ③ polymer monomers with hydrophobic properties.

[0057] The present invention prepares a targeted hydrophobic polymer based on the structural characteristics of AOH to increase the interaction with the target; on this basis, combined with the specific recognition effect of nucleic acid aptamers, a nucleic acid aptamer functionalized magnetic hydrophobic polymer is constructed to achieve rapid and efficient separation and enrichment of AOH with synergistic enhancement of nucleic acid aptamers and magnetic hydrophobic polymers.

[0058] The following examples are used to further illustrate the present invention, but should not be construed as limiting the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the present invention all belong to the scope of the present invention.

[0059] Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. The nucleic acid aptamer of AOH in the following examples was screened by the research team, and its sequence is: 5'-NH2-(CH2)6-GGC ACT CCACGC ATA GGC ATA CTT AAC TAG TGT TCA AGT TAT CCT GTG CGT GGA TGT CC-3', synthesized by Sangon Biotech Co., Ltd.

[0060] Alternaria phenol, Alternaria monomethyl ether (AME), Tenesporic acid (TeA), Tenesporic acid (TEN) and Ochratoxin A (OTA) were purchased from Qingdao Purebon Biotechnology Co., Ltd.

[0061] Polyethylene glycol 200 was purchased from Bitec Pharmaceuticals (Shanghai, China); ethylene glycol, 1,4-dioxane, 3-(trimethoxysilyl)propyl methacrylate (MPS), ferric chloride (FeCl3·6H2O), azobisisobutyronitrile (AIBN), and polyallylamine hydrochloride (PAHC) were purchased from Aladdin (Shanghai, China); methyl methacrylate (MMA), ethyl methacrylate (EMA), butyl methacrylate (BMA), and polyvinylpyrrolidone (PVP) were purchased from Inotech (Beijing, China); ferrous chloride (FeCl3·6H2O), ammonia (NH3·H2O), and tetraethyl orthosilicate (TEOS) were purchased from Beijing Chemical Company (Beijing, China).

[0062] The buffer used was composed of an aqueous solution containing 10.0 mM Tris-HCl, 10.0 mM NaCl, 5.0 mM MgCl2, and a pH of 7.3.

[0063] Example 1

[0064] MHbP was synthesized by free radical polymerization, with MNPs@MPS, VEC and MMA as monomers and AIBN as initiator. Figure 1 The specific operations are as follows:

[0065] (1) Synthesis of Fe3O4 magnetic nanoparticles (MNPs) by hydrothermal method: First, 1.4 g (5.0 mM) FeCl3·6H2O was dissolved in 40 mL ethylene glycol, and then 3.6 g NaAC and 1.0 g polyethylene glycol 200 were added. After stirring for 30 min, the resulting yellow viscous liquid was sealed in a stainless steel autoclave lined with polytetrafluoroethylene and reacted at 200°C for 8 h. After the autoclave was cooled naturally, the generated Fe3O4 MNPs were collected with a magnet, and the excess reactants were washed with ethanol. The product MNPs were stored in deionized water and placed at 4°C for later use.

[0066] (2) Synthesis of MNPs@MPS to introduce double bonds: All the MNPs obtained in the above steps were dispersed in 50 mL of water, 0.5 g of PAHC was added, and the mixture was ultrasonicated for 1 h, and the excess reactants were washed away with deionized water; the above product was added to 10.0 mL of water and 40.0 mL of PVP with a concentration of 50.0 mg / mL, and ultrasonicated for 20 min, stirred at room temperature for 10 h (600 rpm), and the excess reactants were washed away with water; the above product was added to anhydrous ethanol containing 1.3% ammonia by volume (4.6 mL of ammonia and 95.4 mL of ethanol), and then 1.0 mL of TEOS was added, stirred at room temperature for 10 h, and the excess reactants were washed away with ethanol; the above product was then dispersed in 100.0 mL of ethanol, 4.0 mL of MPS was added, and the mixture was stirred at room temperature for 24 h, and the excess reactants were washed away with ethanol. After drying at 45°C for 12 h, it was set aside.

[0067] The above first modified the -C=C- bond on MNPs, and on this basis, the polymer monomers VEC and MMA were polymerized onto MNPs by free radical polymerization. (3) Synthesis of MHbP by free radical polymerization: 100.0 mg MNPs@MPS, 285.0 mg VEC, 500.0 mg MMA, 10.0 mg AIBN and 10.0 mL 1,4-dioxane were added to a flask, and protected with nitrogen, and reacted in an oil bath at 90 ° C for 24 h. The excess reactants on the surface were washed off with ethanol and water, and the obtained product was dried at 45 ° C for 12 h to obtain the magnetic hydrophobic polymer MHbP.

[0068] In order to verify whether the polymerization was successful, MHbP was characterized by infrared spectroscopy (FT-IR), such as Figure 2 In MHbP, at 590.2cm -1 The peak found at 1060.8cm is the characteristic peak of Fe-O in MNPs, indicating that the polymer polymerization process has no obvious effect on MNPs. -1 and 1793.7cm -1 The characteristic absorption peaks found at 1436.9 and 1728.3 cm-1 correspond to the asymmetric stretching vibration and symmetric stretching vibration of -COC- and -C=O- in VEC, respectively. -1 The bending vibration of -CH2- and the stretching vibration of carbonyl group indicate the presence of MMA monomer in MHbP. FT-IR results show that the two functional monomers were successfully grafted onto MNPs.

[0069] After obtaining the magnetic polymer MHbP, the aptamer is coupled by reacting the modified amino group on the aptamer with the epoxy group in VEC to obtain the nucleic acid aptamer functionalized magnetic hydrophobic polymer MHbPA. The specific preparation method is as follows: 10.0μM AOH aptamer (320.0μL) is mixed with 5.0mg of the above-prepared MHbP and incubated at room temperature for 24h. After the reaction is completed, it is washed three times with binding buffer (10.0mM Tris-HCl, 10.0mM NaCl, 5.0mM MgCl2, pH 7.3), and then the excess reactants can be removed on a magnetic stand. After pouring out the liquid, MHbPA is obtained, and then stored in 320μL binding buffer to obtain a concentration of 15.6mg / mL MHbPA, which is stored at 4°C for use. When used, it needs to be separated by a magnetic stand and the supernatant is discarded before use.

[0070] The preparation of MHbPA was confirmed by a series of characterization methods. First, the elemental compositions of MNPs, MHbP, and MHbPA were obtained by X-ray diffraction (XPS), such as Figure 3As shown. Fe2p and O1s peaks can be observed in the spectrum of MNPs; in the spectrum of MHbP, in addition to the peaks of Fe2p and O1s, a peak of C1 was also found, indicating that the polymerization of the polymer monomer introduced the C element; in addition, a N1s peak was also observed in MHbPA, proving that the aptamer was successfully coupled to MHbP.

[0071] The magnetic changes during the synthesis of MHbPA were detected using a vibrating sample magnetometer (VSM). Figure 4 As shown in Figure 2, the magnetic response of MHbPA is related to the content of MNPs. Figure 4 The hysteresis regression curves of MNPs, MHbP and MHbPA are all "S" shaped and symmetrical at the origin, indicating paramagnetism. The saturation magnetization of MNPs, MHbP and MHbPA are 68.7, 49.8 and 39.9 emu / g, respectively. Although the saturation magnetization gradually decreases due to monomer polymerization and aptamer coupling, the retained magnetism is sufficient to achieve rapid separation under the action of an external magnetic field.

[0072] Thermogravimetric analysis (TGA) was used to further verify the MNPs, MHbP and MHbPA. Figure 5 As shown: Since the prepared materials all have a certain amount of residual moisture, their weight decreases slightly at around 100°C; at 200-450°C, the weight of MHbP and MHbPA decreases significantly (about 10%), which is caused by the degradation of the polymer; in addition, the weight loss of MHbPA is about 4% more than that of MHbP, which is caused by the bonding of the aptamer.

[0073] The morphology of the prepared materials and particle size were observed by transmission electron microscopy (TEM). Figure 6 As shown in the figure, all three are uniform spherical particles. The particle sizes of MNPs, MHbP and MHbPA are 196.8±7.0nm, 214.9±2.0nm and 218.4±5.1nm, respectively. Compared with MNPs, the particle size of MHbP has increased significantly, which proves from the morphological level that the polymer has undergone a certain degree of polymerization on the surface of Fe3O4 MNPs; the particle size of MHbPA has increased less than that of MHbP, which may be caused by the flexible structure of the aptamer.

[0074] Example 2

[0075] In order to achieve efficient adsorption of AOH by MHbPA, key factors such as MHbP mass, MHbP composition and adsorption sample volume were investigated.

[0076] Among them, the adsorption efficiency detection method is detected by the following steps:

[0077] AOH adsorption and desorption: 1.0 mL of AOH solution was mixed with 320 μL of 15.6 mg / mL MHbPA prepared according to the method of Example 1 (separated by a magnetic rack and the supernatant was discarded before use) at room temperature for 10 min. After magnetic separation, the supernatant was taken for liquid phase detection, which was the remaining AOH content after MHbPA adsorption; the MHbPA adsorbed with AOH was washed three times with binding buffer, and 0.8 mL of 70% methanol (v / v, methanol / binding buffer) was added and mixed for 10 min. After magnetic separation, the supernatant was taken for liquid phase detection, which was the eluted AOH content.

[0078] High performance liquid chromatography detection method of AOH: The HPLC column is Venusil MP C18 (250×4.6mm id, particle size 5μm, Bonna-Agela China). HPLC detection conditions are: mobile phase A (water)-B (acetonitrile) with 80% A (1min), 80-40% A (3min), 40% A (1min), 40-80% A (1min), 80% A (1min) combined gradient elution; column temperature is 25°C; flow rate is 1.0mL / min; injection volume is 20μL; detector is a fluorescence detector; excitation wavelength is 258nm, emission wavelength is 440nm.

[0079] The adsorption efficiency and recovery rate can be calculated by formula (1) and formula (2), where A0 is the peak area of ​​AOH before adsorption, A1 is the peak area of ​​the supernatant after MHbPA adsorption, and A2 is the peak area of ​​the supernatant after MHbPA elution. The peak areas are integrated on the liquid chromatography software.

[0080]

[0081]

[0082] Investigate the quality of MHbP:

[0083] 10.0μM AOH aptamer (320.0μL) was mixed with 1.0, 3.0, 5.0, 7.0, 9.0, 11.0 and 13.0mg MHbP, respectively, and incubated at room temperature for 24h. After the reaction was completed, it was washed three times with binding buffer (10.0mM Tris-HCl, 10.0mM NaCl, 5.0mM MgCl2, pH 7.3) to remove excess reactants and obtain MHbPA with different MHbP dosages. 320μL of different MHbPAs with a concentration of 15.6mg / mL prepared above (separated by magnetic rack, discarded supernatant and used) were mixed with 1.0mL 1.0μg / mL AOH solution at room temperature for 10min, and after magnetic separation, the supernatant was taken for liquid phase detection. Liquid chromatography was used to detect 1.0 μg / mL AOH (A0) and the peak area (A1) of the supernatant after magnetic separation. The adsorption efficiency was calculated by formula (1). A curve was drawn with the mass of MHbP as the horizontal axis and the adsorption efficiency as the vertical axis. The results are shown in Figure 2. Figure 7 As shown in the figure, the effect of MHbP dosage on AOH adsorption efficiency. The experimental results show that the mass of MHbP has a significant effect on the AOH adsorption efficiency, because MHbP can provide aptamer bonding groups, thereby affecting the concentration of aptamers bonded to MHbPA. The results show that with the increase of MHbP dosage, the adsorption efficiency also increases; when the MHbP concentration is 5.0 mg, the adsorption efficiency of MHbPA for AOH is 92.1%; when the MHbP concentration is 9.0 mg, the adsorption efficiency of MHbPA for AOH increases to 94.2%; the adsorption efficiency of MHbPA for AOH remains stable when the MHbP mass continues to increase (11.0 and 13.0 mg). Considering that the adsorption efficiency of MHbPA is similar, but the dosage of 5.0 mg and 9.0 mg is quite different, 5.0 mg of MHbP was finally selected for the next step of research.

[0084] Investigation of MHbP composition:

[0085] Combining the design principle of MHbPA, that is, the synergistic enhancement of the specific affinity of the aptamer and the hydrophobic interaction of MHbP to achieve the high adsorption performance of MHbPA, the composition of MHbP was investigated.

[0086] MHbP with different hydrophobicity (hydrophobic monomers are MMA, EMA, and BMA, respectively) was synthesized, and different MHbPAs were prepared under the same operating conditions. That is, in the step of synthesizing MHbP by free radical polymerization in Example 1, EMA and BMA were used to replace MMA to conduct experiments and prepare MHbP with different compositions. MHbPA with different compositions of MHbP were prepared according to the method in Example 1. 320 μL of different MHbPA with a concentration of 15.6 mg / mL prepared above (separated by a magnetic rack, and the supernatant was discarded before use) were mixed with 1.0 mL of 1.0 μg / mL AOH solution at room temperature for 10 minutes. After magnetic separation, the supernatant was taken for liquid phase detection. Liquid chromatography was used to detect the peak area (A1) of 1.0 μg / mL AOH (A0) and the supernatant after magnetic separation. The adsorption efficiency was calculated by formula (1). The type of MHbP hydrophobic monomer was used as the horizontal axis and the adsorption efficiency was used as the vertical axis to draw a curve graph. The results are shown in the figure. Figure 8 As shown, this is the effect of different hydrophobic monomers on the adsorption efficiency.

[0087] Figure 8 This indicates that hydrophobicity has a certain influence on the adsorption efficiency, where MMA has the highest adsorption efficiency when used as a hydrophobic monomer, and the adsorption efficiency decreases as the hydrophobicity increases (EMA or MBA as a monomer). The hydrophobic property will promote the hydrophobic interaction with AOH to a certain extent, and the strong hydrophobic property of the monomer may make it difficult for MHbPA to be evenly dispersed in the sample solution, resulting in a decrease in the adsorption efficiency. Therefore, MMA is preferred as a hydrophobic monomer.

[0088] Investigation of monomer polymerization ratio:

[0089] The polymerization ratio of MMA and VEC in MHbP is an important parameter for the composition of MHbP. Seven MHbPs with different mass ratios of MMA and VEC were synthesized. That is, in the step of synthesizing MHbP by free radical polymerization in Example 1, different amounts of VEC and MMA were used to experimentally synthesize MHbP1-7. The specific amounts are shown in Table 1. 5.0 mg of different MHbPs were incubated with 320.0 μL of aptamer solution (10.0 μM) at room temperature for 24 hours. After the reaction was completed, it was washed three times with binding buffer (Tris-HCl, 10.0 mM NaCl, 5.0 mM MgCl2, pH 7.3) to remove excess reactants and obtain MHbPA with different monomer ratios. 320 μL of different MHbPAs with a concentration of 15.6 mg / mL prepared above (separated by magnetic rack, and used after discarding the supernatant) were mixed with 1.0 mL of 1.0 μg / mL AOH solution at room temperature for 10 min. After magnetic separation, the supernatant was taken for liquid chromatography detection. The peak area of ​​1.0 μg / mL AOH (A0) and the supernatant after magnetic separation (A1) were detected by liquid chromatography, and the adsorption efficiency was calculated by formula (1). The results are shown in Table 1, which shows the effect of different monomer-polymer ratios on the adsorption efficiency.

[0090] Table 1 Effect of different VEC and MMA dosage on adsorption efficiency

[0091]

[0092] In Table 1, the MMA dosage was fixed at 500.0 mg to investigate the effect of VEC dosage on adsorption efficiency. As the VEC dosage increased from 70.0 mg to 285.0 mg, the adsorption efficiency increased from 89.1% to 96.9%; when the VEC dosage was 570.0 mg, the adsorption efficiency decreased. The dosage of VEC will affect the bonding amount of the aptamer. The higher the VEC polymerization ratio, the greater the fixed bonding concentration of the aptamer, and the higher the adsorption efficiency; but when the VEC ratio is too high, it will affect the polymerization of MMA, which may lead to a weakening of the synergistic effect and a decrease in adsorption efficiency. Therefore, the preferred MMA:VEC dosage is a mass ratio of 500:70-570, and the most preferred is 500:285.

[0093] The effect of MMA dosage was investigated: keeping the VEC dosage unchanged (285.0 mg), different MMA dosages had a significant effect on the adsorption efficiency. When the MMA polymerization amount was less than 500.0 mg, the adsorption performance of MHbPA on AOH was poor. When the MMA dosage increased to 500.0 mg, the adsorption efficiency was the highest. This shows that the hydrophobic effect in MHbPA is indeed conducive to the adsorption of AOH.

[0094] Investigation of adsorption sample volume:

[0095] MHbPA was prepared according to Example 1. 320 μL of 15.6 mg / mL MHbPA prepared above (separated by magnetic rack, and used after discarding the supernatant) was mixed with 0.5 mL 2.0 μg / mL AOH, 1.0 mL 1.0 μg / mL AOH, 2.0 mL 0.5 μg / mL AOH, 3.0 mL 0.33 μg / mL AOH and 4.0 mL 0.25 μg / mL AOH solution at room temperature for 10 min, and after magnetic separation, the supernatant was taken for liquid chromatography detection. The peak areas of AOH (A0) before adsorption and the supernatant after magnetic separation (A1) were detected by liquid chromatography, and the adsorption efficiency was calculated by formula (1). A curve was drawn with AOH volume as the horizontal axis and adsorption efficiency as the vertical axis. The results are shown in Figure 2. Fig. 9 As shown in the figure, it shows the effect of different sample volumes on the adsorption efficiency. When the sample volume increases from 0.5mL to 1.0mL, the adsorption efficiency increases from 82.9% to 96.9%, while when the sample volume increases to 4.0mL, the adsorption efficiency drops sharply to 56.8%. In order to obtain better AOH adsorption performance, 1.0mL is selected as the optimal sample volume.

[0096] Investigation of desorption solvents:

[0097] MHbPA was prepared according to Example 1. 320 μL of MHbPA prepared above with a concentration of 15.6 mg / mL was separated by a magnetic rack, and the supernatant was discarded and mixed with 1.0 mL of 1.0 μg / mL AOH at room temperature for 10 min. After magnetic separation, the supernatant was collected. The MHbPA adsorbed with AOH was washed three times with binding buffer, and different elution solvents were added: methanol, ethanol, acetonitrile, ultrapure water and 1.0 M NaCl solution were mixed for 10 min. After magnetic separation, the supernatant was taken for liquid phase detection, which is the eluted AOH content. Liquid chromatography was used to detect the AOH peak area before adsorption (A0), the peak area of ​​the supernatant after magnetic separation (A1) and the peak area of ​​AOH eluted with different elution solvents (A2). The recovery rate was calculated by formula (2). A curve graph was drawn with different adsorption solvents as the horizontal axis and the recovery rate as the vertical axis. The results are shown in the figure. Fig.10 As shown in Figure 1, this is the effect of different elution solvents on the recovery rate. Fig.10 Among them, methanol had the highest recovery rate of 88.8%, while the other four solvents were all lower than 60.0%, indicating that the strong interaction between MHbPA and AOH would be sharply weakened after adding methanol. In order to further improve the recovery rate, the proportion of methanol in the desorption solvent was studied.

[0098] Investigation on the ratio of methanol in desorption solvent:

[0099] MHbPA was prepared according to Example 1. 320 μL of 15.6 mg / mL MHbPA prepared above was separated by a magnetic rack, and the supernatant was discarded and mixed with 1.0 mL 1.0 μg / mL AOH at room temperature for 10 min. After magnetic separation, the supernatant was collected. After the MHbPA adsorbed with AOH was washed three times with binding buffer, 0.8 mL of different proportions of methanol were added as elution solvent (methanol and binding buffer were mixed): 50% methanol, 70% methanol, 80% methanol, 90% methanol and 100% methanol were mixed for 10 min. After magnetic separation, the supernatant was taken for liquid phase detection, which was the AOH content eluted when different proportions of methanol were used as elution solvent. Liquid chromatography was used to detect the peak area of ​​AOH before adsorption (A0), the peak area of ​​the supernatant after magnetic separation (A1), and the peak area of ​​AOH eluted with different elution solvents (A2). The recovery rate was calculated by formula (2). A curve was drawn with the methanol ratio as the horizontal axis and the recovery rate as the vertical axis. The results are shown in Figure 2. Fig.11 As shown in the figure, the effect of different methanol ratios on the recovery rate. When the methanol ratio is 50%, the recovery rate is the lowest; when the methanol ratio is 70%, the recovery rate is the highest, 93.4%. Therefore, a mixture of 30% binding buffer and 70% methanol is used as the desorption solvent.

[0100] Investigation of desorption time:

[0101] MHbPA was prepared according to Example 1. 320 μL of MHbPA prepared above with a concentration of 15.6 mg / mL was separated by a magnetic rack, and after discarding the supernatant, it was mixed with 1.0 mL of 1.0 μg / mL AOH at room temperature for 10 min. After magnetic separation, the supernatant was collected. The MHbPA adsorbed with AOH was washed three times with binding buffer, and 0.8 mL of 70% methanol was added as an elution solvent and mixed for 10, 20, 30, 60, 120, 240 and 360 min respectively. After magnetic separation, the supernatant was taken for liquid phase detection, which is the AOH content eluted when different methanol ratios are used as the elution solvent. Liquid chromatography was used to detect the AOH peak area before adsorption (A0), the peak area of ​​the supernatant after magnetic separation (A1), and the peak area of ​​AOH eluted at different elution times (A2). The recovery rate was calculated by formula (2). A curve graph was drawn with the elution time as the horizontal axis and the recovery rate as the vertical axis. The results are shown in the figure. Fig.12 As shown in the figure, the effect of different elution times on the recovery rate. The recovery rate increased significantly from 0 to 10 minutes, and as the desorption time continued to increase, the recovery rate did not increase significantly, indicating that the desorption of MHbPA can be completed in a shorter desorption time, which greatly reduces the pretreatment time of the actual sample. The preferred elution time is 10 to 60 minutes. In order to quickly realize the AOH sample pretreatment process, 10 minutes is selected as the optimal desorption time for MHbPA.

[0102] Investigation of desorption volume:

[0103] MHbPA was prepared according to Example 1. 320 μL of MHbPA prepared above with a concentration of 15.6 mg / mL was separated by a magnetic rack, and after discarding the supernatant, it was mixed with 1.0 mL of 1.0 μg / mL AOH at room temperature for 10 min. After magnetic separation, the supernatant was collected. After washing the MHbPA adsorbed with AOH three times with binding buffer, 0.2, 0.4, 0.6, 0.8 and 1.0 mL of 70% methanol were added as elution solvents and mixed for 10 min. After magnetic separation, the supernatant was taken for liquid phase detection, which is the AOH content eluted with different volumes of elution solvent. Liquid chromatography was used to detect the AOH peak area (A0) before adsorption, the peak area of ​​the supernatant after magnetic separation (A1) and the peak area (A2) of AOH eluted at different elution times. The recovery rate was calculated by formula (2) (replacing 0.8 with the corresponding elution volume). A curve graph was drawn with the elution volume as the horizontal axis and the recovery rate as the vertical axis. The results are shown in the figure. Fig.13 The experimental results show that the recovery rate increases with the increase of desorption volume, and reaches the maximum value when the desorption volume is 0.8 mL. Therefore, the desorption volume of 0.8 mL is selected, and the enrichment effect is 1.25 times.

[0104] Example 3

[0105] Isothermal adsorption experiment:

[0106] MHbPA was prepared according to Example 1. 320 μL of 15.6 mg / mL MHbPA prepared above was mixed with 1.0 mL of 0.5, 0.6, 0.8, 1.0, 2.0 and 5.0 μg / mL AOH at room temperature for 10 min, respectively. After magnetic separation, the supernatant was collected. The AOH peak area before adsorption (A0) and the peak area of ​​the supernatant after magnetic separation (A1) were detected by liquid chromatography. The adsorption efficiency was calculated by formula (1), and the adsorption capacity Q was calculated by formula (3). A curve was drawn with AOH concentration as the horizontal axis and adsorption efficiency and adsorption capacity as the vertical axis. The results are shown in Figure 2. Fig.14 The adsorption isotherm of MHbPA is shown in Figure 2. Fig.14 In the experiment, with the increase of AOH concentration, the adsorption efficiency gradually decreased, and the adsorption capacity gradually increased, with the maximum value of 187.6 ng / mg.

[0107] The above data were fitted according to the Langmuir adsorption model and the Freundlich adsorption model using the origin software through formula (4) and formula (5), and the following equation was obtained: Fig.15In the Langmuir adsorption model, the saturated adsorption capacity of MHbPA was 190 ng / mg; the fitting result of the Freundlich adsorption model was poor (R 2 Therefore, the adsorption type of MHbPA is closer to the Langmuir model, indicating that the adsorption of MHbPA on AOH is a monolayer adsorption.

[0108]

[0109]

[0110]

[0111] Where C0 is the initial concentration of AOH before adsorption, C e is the concentration of AOH after adsorption, i.e., the residual concentration (mg / L), V is the volume of AOH, m is the amount of MHbPA (mg), Q m is the saturated adsorption capacity (mg / g), K L is the Langmuir constant (L / mg), K F is the Freundlich adsorption constant (mg / g), n is a constant. Adsorption kinetics:

[0112] MHbPA was prepared according to Example 1. 320 μL of 15.6 mg / mL MHbPA prepared above was mixed with 1.0 mL of 1.0 μg / mL AOH at room temperature for 0.5, 1, 3, 5, 10, 20, 60 and 120 min, respectively. After magnetic separation, the supernatant was collected. Liquid chromatography was used to detect the AOH peak area before adsorption (A0) and the peak area of ​​the supernatant after magnetic separation (A1), and the adsorption efficiency was calculated by formula (1). A curve was drawn with the mixing incubation time as the horizontal axis and the adsorption efficiency as the vertical axis. The results are shown in Figure 1. Fig.16 The adsorption kinetics of MHbPA are shown in Fig. Fig.16 In the experiment, the adsorption efficiency increased significantly from 0.5min to 10min and reached a plateau after 10min.

[0113] The adsorption kinetics of the above data were calculated and fitted according to the pseudo first-order kinetic model and pseudo second-order kinetic model by using formula (6) and formula (7) and using origin software to obtain Fig.17 The adsorption of MHbPA on AOH is more consistent with the pseudo-second-order adsorption kinetic model. 2 The adsorption reached equilibrium within 10 min, and the equilibrium adsorption amount was 186.0 ng / mg, which was consistent with the experimental results.

[0114] ln(Q e-Q t )=ln Q e -K1t (6)

[0115]

[0116] Q e is the adsorption amount at adsorption equilibrium (mg / g), Q t is the adsorption amount (mg / g) at any time t (min), K1 is the pseudo-first-order kinetic equilibrium constant (1 / min), and K2 is the pseudo-second-order kinetic equilibrium constant (g / mg·min).

[0117] Example 3 shows that the adsorption type of MHbPA on AOH is closer to the Langmuir model, indicating that the adsorption of MHbPA on AOH is monolayer adsorption; the kinetic adsorption is more consistent with the pseudo-secondary adsorption kinetic model. The maximum adsorption capacity is 187.6 ng / mg, and the optimal adsorption time is 10 min, which can achieve efficient adsorption of AOH in a relatively short time.

[0118] Example 4

[0119] MHbPA was prepared according to Example 1, and the adsorption process was carried out according to the steps of Example 2, except that the targets were replaced with five mycotoxins, namely AME, TeA, TEN, OTA and DON, to evaluate the selectivity of the adsorbent MHbPA. 1.0 μg / mL of different mycotoxins were mixed and incubated with 320 μL of 15.6 mg / mL MHbPA, and after 10 minutes, the supernatant was magnetically separated and subjected to HPLC determination.

[0120] The adsorption capacity Q is calculated by formula (3) Fig.18 In the results, because AME and AOH have similar structures, the adsorption capacity of AME is higher (this is related to the selectivity of nucleic acid aptamers). In addition, the adsorption capacity of hydrophobic small molecule fungal toxins such as TEN and OTA is between 30-40 ng / mL (the adsorption capacity of TeA is 3.6 ng / mg), which is relatively high, indicating that the hydrophobic interaction between the polymer and the hydrophobic molecules does promote adsorption. However, the adsorption capacity is much lower than that of MHbPA, proving that the synergistic effect of the polymer and the aptamer enhances the adsorption performance, and the aptamer also ensures the recognition specificity. It shows that MHbPA has good selectivity and high adsorption capacity for AOH as an adsorbent.

[0121] MHbPA was prepared according to Example 1, and after being stored in the binding buffer for 4 weeks, the adsorption process was carried out according to the steps of Example 2, and the adsorption efficiency was calculated according to formula (1) to investigate the stability of MHbPA. Fig.19The adsorption efficiency of MHbPA for AOH remained above 80% after 4 weeks of storage, showing good stability. Fig. 20 In the present invention, after the MHbPA is reused for 6 times, the adsorption efficiency is still maintained above 80%, showing good reusability.

[0122] Example 5

[0123] In order to evaluate the feasibility of MHbPA adsorbent for adsorption of AOH in actual samples, it was applied to the identification and adsorption of AOH in three wheat flour samples spiked with AOH. 5.0 g of wheat flour was mixed with 10.0 mL of water / acetonitrile (40 / 60, v / v) in a centrifuge tube and vortexed for 10 min. The supernatant was filtered through a filter membrane and then AOH of different concentrations was added. The mixture was diluted 10 times with binding buffer. The final AOH concentrations were 250.0 ng / mL, 375.0 ng / mL, and 500.0 ng / mL, respectively. Three wheat flour samples spiked with different concentrations of AOH were mixed with 320 μL of 15.6 mg / mL MHbPA prepared according to Example 1 and incubated for 10 min. After magnetic separation, the supernatant was taken, and the MHbPA adsorbed with AOH was washed three times with binding buffer, and then mixed with 0.8 mL of 70% methanol (methanol / binding buffer, v / v, 70 / 30) and incubated for 10 min to elute the adsorbed AOH. After magnetic separation, the supernatant was taken for HPLC determination, which was the AOH content eluted after MHbPA adsorption.

[0124] According to the liquid chromatography detection method, different concentrations of AOH standard products (10ng / mL, 50ng / mL, 100ng / mL, 500ng / mL, 1000ng / mL, 2000ng / mL) were detected, and the peak areas of different concentrations of AOH were integrated on the liquid chromatography workstation. A linear fit was performed with AOH concentration as the horizontal axis and peak area as the vertical axis, and the linear equation was obtained as Y=0.13X-0.52(R 2 =0.990), and each group of experiments was measured in triplicate.

[0125] Substituting the peak area (Y value) of AOH after elution into the linear equation of AOH liquid chromatography Y=0.13X-0.52, the concentration (X value) of AOH after elution can be obtained. Since the volume of the eluent is 0.8 mL, the final elution concentration of AOH of 1 mL sample is obtained by multiplying the concentration of the eluent by 0.8. The spike recovery rate is calculated according to formula (8), and the results are shown in Table 2. In Table 2, the recovery rate of MHbPA for AOH in actual wheat samples ranges from 81.4% to 105.9%, indicating that it still has good adsorption capacity in actual samples.

[0126] Where C0 is the spiked concentration of AOH, and C2 is the concentration of AOH after elution.

[0127] Table 2 Recovery of MHbPA for AOH in actual spiked wheat samples

[0128]

[0129]

[0130] Example 6

[0131] Method for determining the content of AOH in the sample to be tested: 5.0 g of the sample to be tested was mixed with 10.0 mL of water / acetonitrile (40 / 60, v / v) in a centrifuge tube, vortexed for 10 min, the supernatant was filtered through a filter membrane, and the mixture was diluted 10 times with a binding buffer. 1.0 mL of the above sample solution was mixed with 320 μL of 15.6 mg / mL MHbPA prepared in Example 1 (separated by a magnetic rack, and the supernatant was discarded before use) and incubated for 10 min. After magnetic separation, the MHbPA adsorbed with AOH was washed three times with a binding buffer, and then mixed with 0.8 mL of 70% methanol (methanol / binding buffer, v / v, 70 / 30) and incubated for 10 min to elute the adsorbed AOH. After magnetic separation, the supernatant was taken for HPLC determination, which was the AOH content eluted after MHbPA adsorption. Each group of experiments was measured three times in parallel. The peak area (Y value) of AOH after elution was substituted into the linear equation of AOH liquid chromatography Y=0.13X-0.52 to obtain the concentration (X value) of AOH after elution. Since the volume of the eluent is 0.8 mL, the concentration of the eluent is multiplied by 0.8 to obtain the final elution concentration of AOH of 1 mL sample. On this basis, this value is expanded by 10 times to obtain the content of AOH in the sample to be tested.

[0132] Comparative Example 1

[0133] MNPs were prepared according to Example 1, and MNPs (MNP-Apt) bonded with appropriate ligands were prepared according to the MHbPA preparation method, that is, MHbP was replaced with MNPs during the MHbPA preparation process.

[0134] MNP@pVEC was prepared by removing the MMA monomer in the preparation process according to the method for preparing MHbP in Example 1. MNP@pVEC-Apt was prepared according to the method for preparing MHbPA, that is, MHbP was replaced with MNP@pVEC in the preparation process of MHbPA.

[0135] MHbP was prepared according to the method in Example 1.

[0136] MHbPA was prepared according to the method in Example 1.

[0137] The four materials prepared above were used as adsorbents respectively, and AOH adsorption was carried out according to the operating steps of Example 2. The adsorption efficiency was calculated according to formula (3). A bar graph was drawn with different adsorbents as the horizontal axis and adsorption efficiency as the vertical axis. The results are shown in Fig.21 . Compared with MNP-Apt, MNP@pVEC-Apt showed better adsorption capacity, and the polymerization of VEC on MNPs provided more aptamer bonding groups. Compared with MHbP, MHbPA had a higher adsorption capacity, which was 4 times that of MHbP. In addition, the adsorption capacity of MHbPA for AOH was also significantly higher than that of MNP@pVEC-Apt. The results show that a higher adsorption capacity cannot be obtained solely by the affinity between the aptamer and AOH or the hydrophobic interaction between the polymer and AOH. Enhanced adsorption can only be achieved under the synergistic effect of the affinity of the aptamer and the hydrophobic effect of the polymer.

[0138] The above results indicate that the MHbPA prepared in the present invention has strong adsorption performance with AOH.

[0139] Comparative Example 2

[0140] The performance of the adsorbent prepared by the present invention was compared with the adsorption effects of different fungal toxins reported in the literature, and the results are shown in Table 3.

[0141] Table 3 Comparison of adsorption effects of different adsorbents on different fungal toxins

[0142]

[0143] The above comparison results show that the MHbPA prepared by the present invention has the advantages of high efficiency and rapidity in adsorbing AOH.

Claims

1. A cross-linked spore phenol adsorbent based on nucleic acid aptamer functionalized magnetic hydrophobic polymer, characterized in that: The invention is obtained by coupling a nucleic acid aptamer with a magnetic hydrophobic polymer. The magnetic hydrophobic polymer is a copolymer of magnetic nanoparticles, methyl methacrylate and vinyl ethylene carbonate. The nucleic acid aptamer is used for specifically binding to cross-linked spore phenol. The nucleic acid sequence of the nucleic acid aptamer is: 5'-NH2-(CH2)6-GGCACTCCACGCATA GGCATACTTAACTAGTGTTCAAGTTATCCTGTGCGTGGATGT CC-3'; The magnetic hydrophobic polymer material is prepared by the following method: adding magnetic nanoparticles to a polyallylamine hydrochloride solution for a first ultrasonic washing, then adding a polyvinyl pyrrolidone solution for a second ultrasonic reaction, and then stirring for a first reaction, washing with water, adding the magnetic nanoparticles and tetraethyl orthosilicate to anhydrous ethanol containing ammonia water, stirring for a second reaction, and then washing with ethanol to remove excess reactants; then dispersing the magnetic nanoparticles in ethanol, adding 3-(trimethoxysilyl)propyl methacrylate, and stirring for a third time to synthesize MNPs@MPS; The magnetic polymer material MHbP was synthesized by reacting MNPs@MPS with VEC, MMA, AIBN and 1,4-dioxane; The magnetic nanoparticles and PAHC are added in a mass ratio of 2:1, the amount of polyvinyl pyrrolidone and PAHC are added in a mass ratio of 1:4, the ratio of tetraethyl orthosilicate to 1.3% ammonia water and anhydrous ethanol is 1:100, and the ratio of 3-(trimethoxysilyl)propyl methacrylate to ethanol is 1:25; MNPs@MPS was reacted with VEC, MMA, AIBN and 1,4-dioxane in a mass to volume ratio of 100:70 to 570:500:10:10, where the first four were in mass units of mg and the last one was in volume units of mL; the reaction conditions for synthesizing MHbP were nitrogen protection and a 90°C oil bath for 24 hours.

2. The cross-linked spore phenol adsorbent according to claim 1, characterized in that: The first ultrasonic time is 1 to 60 minutes, and the second ultrasonic time is 15 to 30 minutes; the first stirring time is 5 to 10 hours, the second stirring time is 5 to 10 hours, and the third stirring time is 10 to 24 hours.

3. The cross-linked spore phenol adsorbent according to claim 1, characterized in that: After incubation of the magnetic hydrophobic polymer material with the AOH aptamer, a cross-linked spore phenol adsorbent of a nucleic acid aptamer functionalized magnetic hydrophobic polymer, namely MHbPA, was obtained; the reaction ratio of MHbP to the AOH aptamer solution was 5.0 mg: 320.0 μL, the concentration of the AOH aptamer was 10.0 μM, the incubation time was 24 h, and it was carried out at room temperature.

4. A method for preparing a cross-linked spore phenol adsorbent based on a nucleic acid aptamer functionalized magnetic hydrophobic polymer, characterized in that: It includes the following steps: S1. Preparation of magnetic nanoparticles (MNPs): First, 1.4 g (5.0 mM) FeCl3·6H2O was dissolved in 40 mL ethylene glycol, and then 3.6 g NaAC and 1.0 g polyethylene glycol 200 were added. After stirring for 30 min, the obtained yellow viscous liquid was sealed in a stainless steel autoclave lined with polytetrafluoroethylene and reacted at 200°C for 8 h. After the autoclave was cooled naturally, the generated MNPs were collected with a magnet, and the excess reactants were washed away with ethanol to obtain MNPs. S2. Disperse the above MNPs in 50 mL of water, add 0.5 g of PAHC, sonicate for 1 h, and wash away excess reactants with deionized water; add 10.0 mL of water and 40.0 mL of 50.0 mg / mL PVP to the above product, sonicate for 20 min, stir at 600 rpm for 10 h at room temperature, and wash away excess reactants with water; add the above product to 100 mL of anhydrous ethanol containing 1.3% ammonia, add 1.0 mL of TEOS, stir at room temperature for 10 h, and wash away excess reactants with ethanol; disperse the above product in 100.0 mL of ethanol, add 4.0 mL of MPS, stir at room temperature for 24 h, wash away excess reactants with ethanol, and dry at 45 ° C for 12 h to obtain MNPs@MPS; S3. Preparation of magnetic hydrophobic polymer: 100.0 mg MNPs@MPS, 285.0 mg VEC, 500.0 mg MMA, 10.0 mg AIBN and 10.0 mL 1,4-dioxane were added into a flask, and the mixture was protected with nitrogen and reacted in an oil bath at 90 °C for 24 h. The excess reactants on the surface were washed off with ethanol and water, and the obtained product was dried at 45°C for 12 h to obtain MHbP; S4, 320.0 μL of 10.0 μM AOH aptamer was mixed with 5.0 mg MHbP and incubated at room temperature for 24 h; after the reaction was completed, the mixture was washed three times with binding buffer to remove excess reactants and obtain MHbPA; The binding buffer is an aqueous solution containing 10.0 mM Tris-HCl, 10.0 mM NaCl, 5.0 mM MgCl2, pH 7.

3.

5. Use of the interlaced spore phenol adsorbent according to any one of claims 1 to 3 or the interlaced spore phenol adsorbent obtained by the preparation method according to claim 4 in sample pretreatment for detecting AOH.

Citation Information

Patent Citations

  • Nucleic acid aptamer-molecular imprinting synergistic recognition magnetic microspheres and preparation method and application thereof

    CN108659255A